2016
DOI: 10.1097/tp.0000000000001001
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Transnational Transplant-Related Crimes—What More Can be Done?

Abstract: States are encouraged to include provisions on extraterritorial jurisdiction in their laws on transplant-related crimes and to collaborate with professionals and international authorities in the development of a global registry of transnational transplant activities. These actions would assist in the identification and evaluation of illicit activities and provide information that would help in developing strategies to deter and prevent them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 36 publications
2
27
0
Order By: Relevance
“…Special emphasis should be given to family systems and dynamics, and assessment for the presence of coercion, undue pressure, or financial motivation . Socioeconomic stability should be assessed, including review of donor candidate's lifestyle and occupation, and confirmation of gainful employment and/or financial support from family.…”
Section: Comprehensive Evaluationmentioning
confidence: 99%
“…Special emphasis should be given to family systems and dynamics, and assessment for the presence of coercion, undue pressure, or financial motivation . Socioeconomic stability should be assessed, including review of donor candidate's lifestyle and occupation, and confirmation of gainful employment and/or financial support from family.…”
Section: Comprehensive Evaluationmentioning
confidence: 99%
“…Various commentators have suggested that requiring the reporting of this information, for example to a central public health authority, would help to combat transplant tourism by providing information about the nature and scope of the phenomenon and would potentially facilitate follow-up by regulators in the relevant jurisdiction. 6,9,10 The potential merits of such a reporting scheme present an opportunity for modest, yet valuable, legal reform in Canada. Existing health information legislation could be amended to create a reporting system that permits or even requires physicians to provide basic information about suspected transplant tourism, including the location and any known details about the organ transplant network.…”
Section: Key Pointsmentioning
confidence: 99%
“…International collaboration and multifaceted strategies are needed to address the complex challenges of TT. The introduction of registries for foreign transplant donors and recipients and for recipients and donors who receive surgery abroad is an essential component of this work (6).…”
Section: To the Editormentioning
confidence: 99%